Analysis Of Land And Building Tax According To Islamic Economic Perspective - Yoga Tantular Rachman (Universitas Pendidikan Indonesia, 2023)
This study aims to analysis of land and building taxes from the perspective of Islamic economics, uses a type of descriptive qualitative research. Sources of data and data collection for this study were obtained from library research, observation, interview and internet. The data analysis used is the data analysis model of Miles and Huberman. A data validity test in qualitative research includes credibility, transferability, dependability, and objectivity. According to the findings of this study, in Islamic economics, land and building taxes is synonymous with the term kharaj, it's just that kharaj during the Rosulullah SAW era was imposed only on non-Muslims. In Indonesia, taxes including land and building taxes are permissible by most ulema (jumhur ulema) as long as they are not included in the category of mukus or usry. So that the results of the analysis of land and building tax according to the Islamic Economic Perspective are in accordance with Islamic law as long as they are not included in the mukus or usry category, where land and building tax revenue is used for the construction of public facilities for the benefit of society and social justice in the ability of taxpayers to pay land tax and buildings.